Gabrielle de Coignard’s Sonnets spirituels: Writing Passion within and against the Petrarchan Tradition - Lesko Baker, Deborah (Renaissance and Reformation / Renaissance et Réforme, 2015)
This article will focus on the ways in which Gabrielle de Coignard’s Sonnets spirituels, cultivated in purposefully sought domestic isolation, reveals conflictual aspirations nourished by the pursuit of an untainted devotional path that nevertheless cannot escape the assimilation of the earthly passion-fraught discourse of the Petrarchan tradition. Beginning with an analysis of the two opening sonnets, I will examine how despite her apparent disavowal of the worldly obsessions of practitioners of this dominant tradition in order to define herself as a singularly and purely Christian poet, her writing places many of their conventions, allusions, and rhetoric at the centre of her own poetic itinerary. I will then move on to study how these opening signals of Coignard’s inscription of her devotional trajectory both against and within the male and female Petrarchan tradition are affirmed at multiple moments in the progression of her collection.